Factors Supporting and Threatening the Adolescence of Transplanted Youth – Resilience, Well-Being, and Difficulty with Chronic Illness - KÖVESDI, Andrea; TAKÁCS, Szabolcs; RÓZSA, Sándor; KRIKOVSZKY, Dóra; KOVÁCS, Lajos; DEZSŐFI-GOTTL, Antal; SZABÓ, Attila (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2025)
Objective: The present research investigated the proportion of vulnerable and protective factors in terms of mental health in transplanted adolescents compared to the age-matched control group. Method: We collected data using a complex procedure; questionnaires, interviews and projective tests involving transplanted adolescents at the 1st Department of Pediatrics of Semmelweis University. In this work, we present the results of the analysis of the questionnaires. The sample included 59 transplanted and 116 control group members. Results: We found differences between the groups, with the transplanted adolescents being more likely to have depressive mood, more intense experience of anxiety states and stress, and well-being. Parents of transplanted adolescents were also more likely to have depressive mood and anxiety states. The members of the control group were characterized by self-efficacy, emotion-focused coping, and prosocial behavior. We found no differences between the groups in terms of resilience. Conclusions: The optimal development of transplanted youth is hampered by depression, anxiety and stress management problems, and their exposure to risk factors is significant. In the case of transplanted adolescents and their parents, negative emotional overload is typical, therefore we recommend integrative and psychotherapeutic assistance for them.